SOCIAL DIALOGUE AS TOOL FOR INTEGRATION OF GENDER EQUALITY INTO LABOR SPHERE BY AUTHORITIES (Case Study: KHARKIV) - Sychova V.V.; Kindiakova K.S. (Pressing Problems of Public Administration, 2015)
The paper presents results of gender expert evaluation of 5,000 collective agreements, registered with directorates of labor and social security of district administrations of Kharkiv City Council in 2010-2014. It has been found that most of them are not gender-sensitive. A tendency is observed towards a growing number of collective agreements, which contain a gender component. It has been substantiated that it is local government bodies which can apply a social dialogue at the local level as an effective tool for gender equality integration into the labor sphere.